Dysregulation of systemic soluble immune checkpoints in early breast cancer is attenuated following administration of neoadjuvant chemotherapy and is associated with recovery of CD27, CD28, CD40, CD80, ICOS and GITR and substantially increased levels of PD-L1, LAG-3 and TIM-3 - Rapoport, Bernardo L.; Steel, Helen C.; Benn, Carol A.; Nayler, Simon; Smit, Teresa; Heyman, Liezl; Theron, Annette J.; Hlatshwayo, Nomsa; Kwofie, Luyanda L.I.; Meyer, Pieter W.A.; Anderson, Ronald (Frontiers in Oncology, 2023)
Neoadjuvant chemotherapy (NAC) may alter the immune landscape of patients with early breast cancer (BC), potentially setting the scene for more effective implementation of checkpoint-targeted immunotherapy. This issue has been investigated in the current study in which alterations in the plasma concentrations of 16 soluble co-stimulatory and co-inhibitory, immune checkpoints were measured sequentially in a cohort of newly diagnosed, early BC patients (n=72), pre-treatment, post-NAC and post-surgery using a Multiplex® bead array platform. Relative to a group of healthy control subjects (n=45), the median pre-treatment levels of five co-stimulatory (CD27, CD40, GITRL, ICOS, GITR) and three co-inhibitory (TIM-3, CTLA-4, PD-L1) soluble checkpoints were significantly lower in the BC patients vs. controls (p<0.021-p<0.0001; and p<0.008-p<0.00001, respectively). Following NAC, the plasma levels of six soluble co-stimulatory checkpoints (CD28, CD40, ICOS, CD27, CD80, GITR), all involved in activation of CD8+ cytotoxic T cells, were significantly increased (p<0.04-p<0.00001), comparable with control values and remained at these levels post-surgery. Of the soluble co-inhibitory checkpoints, three (LAG-3, PD-L1, TIM-3) increased significantly post-NAC, reaching levels significantly greater than those of the control group. PD-1 remained unchanged, while BTLA and CTLA-4 decreased significantly (p<0.03 and p<0.00001, respectively). Normalization of soluble co-stimulatory immune checkpoints is seemingly indicative of reversal of systemic immune dysregulation following administration of NAC in early BC, while recovery of immune homeostasis may explain the increased levels of several negative checkpoint proteins, albeit with the exceptions of CTLA-4 and PD-1. Although a pathological complete response (pCR) was documented in 61% of patients (mostly triple-negative BC), surprisingly, none of the soluble immune checkpoints correlated with the pCR, either pre-treatment or post-NAC. Nevertheless, in the case of the co-stimulatory ICMs, these novel findings are indicative of the immune-restorative potential of NAC in early BC, while in the case of the co-inhibitory ICMs, elevated levels of soluble PD-L1, LAG-3 and TIM-3 post-NAC underscore the augmentative immunotherapeutic promise of targeting these molecules, either individually or in combination, as a strategy, which may contribute to the improved management of early BC.